Study Determination About Receivers of Support for Rehabilitation "The Houses Unhabitable" in Slum Area, Indonesia - Boby Rahman; Dhea Fina Ramadhanty; Mohammad Agung Ridlo (Pondasi, 2021)
Abstract. Indonesia, a developing country, has launched a program with a target of 0% slum in urban areas by 2020. It has been more than ten years since this program for handling urban slums has made many improvements. One aspect of the parameter that becomes an improvement in handling urban slum areas is the improvement of uninhabitable houses. This study investigates how the quality of urban slum settlements can be improved in the aspect of houses that are not habitable, especially in terms of determining the recipient of rehabilitation assistance for houses that are unhabitable in urban areas. This study used a qualitative methodology and analysis of the literature review in 21 scientific papers on selecting houses that are not habitable assistance and related regulations. The result is that there are two processes in determining Receivers of Support for Rehabilitation "The Houses Unhabitable", first through the aspects of the criteria for houses unhabitable which are technical in the field, and selection techniques that are more academic in nature. Aspects of the criteria for houses unhabitable provide an assessment of the area and buildings. whereas the selection technique requires a selection technique capable of managing data that has many criteria.